Turbulence of shear flows of magnetized plasma - Mikhailenko, V.S.; Stepanov, K.N.; Mikhailenko, V.V.; Azarenkov, N.A.; Chibisov, D.V. (Вопросы атомной науки и техники, 2009)
The presented report summarizes authors' recent results in the analytical investigation of turbulence of the magnetized
plasma shear flows. The emphasis are made on low frequency turbulence of drift type in flows with strongly
inhomogeneous shear with application to improved confinement regimes in toroidal plasma and on ion cyclotron
turbulence in shear flows along the ambient magnetic field with applications to anomalous ions heating in ionosphere. Дано огляд нових результатів авторів з аналітичного дослідження турбулентності зсувних течій плазми у
магнітному полі. Розглянуто дрейфову турбулентність плазми у течіях з сильно неоднорідним градієнтом
швидкості течії з застосуваннями до режимів поліпшеного утримання тороїдальної плазми та іонну
циклотронну турбулентність зсувних течій плазми вздовж магнітного поля із застосуванням до аномального
нагрівання іонів у іоносфері. Дан обзор новых результатов авторов по аналитическому исследованию турбулентности сдвиговых течений
плазмы в магнитном поле. Рассмотрена дрейфовая турбулентность в течениях плазмы с сильно неоднородным
градиентом скорости течения с приложениями к режимам улучшенного удержания тороидальной плазмы и
ионная циклотронная турбулентность сдвиговых течений плазмы вдоль магнитного поля с приложениями к
аномальному нагреву ионов в ионосфере.